Prarancangan Pabrik Fenol Dan Aseton Dari Cumene Dengan Proses Kbr Dengan Disain Alat Utama Reaktor Hidrogenasi (R-103) - Sitinjak, Monaeka; Heltina, Desi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Phenol or hydroxybenzene is an organic compound which is widely used. Phenols are also used to produce various substances such as bisphenol-A, phenolic resins, caprolactam, alkyl phenols, and anilines. Acetone is used as a solvent for gums, waxes, resins, oils, dyes and cellulose because it has excellent dissolving properties. The wide use of these materials causes the domestic demand for phenol and acetone to increase every year. This chemical plant is designed to produce phenol and acetone with a capacity of 30,000 tonnes per year. One of the main equipment in this plant is the hydrogenation reactor (R-103). This equipment is designed for the hydrogenation reaction scene between alpha methyl styrene (AMS) and hydrogen. The output of the reactor is in the form of cumene which will be recycled to be fed to M-101 and then used as raw material for making CHP on R-101. This type of reactor is a bubble column reactor using a cooling jacket and is operated at a temperature of 388.15 K and a pressure of 3.039 bar. The liquid feed flow rate is 1353,6109 kg per hour. The gas feed flow rate is 51,274 kg per hour, consisting of cumene and AMS for liquid feed and hydrogen for gas feed. The reactor height is 2,875 m, diameter of 1.3716 with a support and head types, namely torispherical and dished. Economic analysis is carried out to see the feasibility of the factory. Based on the economic feasibility analysis, the phenol and acetone factories were feasible to be built with a 4-year PBP, 13.039% IRR, 25.03% ROI, and 50% BEP. Keywords: phenol, acetone, hydrogenation, reactor bubble column, economic analysis